2018
DOI: 10.1038/s41558-018-0254-2
|View full text |Cite
|
Sign up to set email alerts
|

Climate warming leads to divergent succession of grassland microbial communities

Abstract: Accurate climate projections require an understanding of the effects of warming on ecological communities and the underlying mechanisms that drive them 1-3 . However, little is known about the effects of climate warming on the succession of microbial communities 4,5 . Here we examined the temporal succession of soil microbes in a long-term climate change experiment at a tall-grass prairie ecosystem. Experimental warming was found to significantly alter the community structure of bacteria and fungi. By determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
186
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 258 publications
(228 citation statements)
references
References 53 publications
(88 reference statements)
20
186
0
1
Order By: Relevance
“…Our results contribute to a growing body of literature indicating that soil microbial community structure cannot be well predicted based on projected changes in climate alone (Guo et al, ; Gutknecht et al, ; Tu et al, ; Waldrop et al, ), and highlight the importance of relatively unpredictable variables in regulating microbial communities. Future studies should aim to not only reduce the uncertainty surrounding wildfire risk and plant community succession, but also to identify the environmental contexts under which these variables are relevant controls on soil microbial communities.…”
Section: Resultssupporting
confidence: 56%
See 1 more Smart Citation
“…Our results contribute to a growing body of literature indicating that soil microbial community structure cannot be well predicted based on projected changes in climate alone (Guo et al, ; Gutknecht et al, ; Tu et al, ; Waldrop et al, ), and highlight the importance of relatively unpredictable variables in regulating microbial communities. Future studies should aim to not only reduce the uncertainty surrounding wildfire risk and plant community succession, but also to identify the environmental contexts under which these variables are relevant controls on soil microbial communities.…”
Section: Resultssupporting
confidence: 56%
“…These effects may be taxon‐specific, however, as the abundance of arbuscular mycorrhizal fungi increased within the elevated‐CO 2 plots (Antoninka, Reich, & Johnson, ). In another long‐term experiment, Guo et al () found that grassland microbial communities under a warming treatment initially showed unpredictable divergences in composition which were later followed by convergences, perhaps as a result of environmental filtering induced by long‐term warming.…”
Section: Introductionmentioning
confidence: 99%
“…Temperature is known to influence soil microbial community structure (Davidson and Janssens, ; Leininger et al ., ; Jurburg et al ., ). Climate warming accelerates temporal turnover and divergent succession of soil microbial communities (Guo et al ., , ). Species diversity, metabolic activity and population growth rates increase exponentially with temperature (Zhou et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Among the niche‐based processes, homogeneous selection tended to dominate, suggesting that similar environmental conditions across islands imposed significant selective force that resulted in greater similarity in the structure of soil bacterial communities than expected by chance. Recent research has identified the importance of a host of environmental factors, such as climate (Maestre et al ., ; Zhou et al ., ; Guo et al ., ; Delgado‐Baquerizo et al ., ), salinity (Lozupone and Knight, ; Thompson et al ., ), soil pH (Fierer and Jackson, ; Thompson et al ., ; Delgado‐Baquerizo et al ., ) and nutrient availability (Ramirez et al ., ; Ramirez et al ., ; Leff et al ., ), in shaping bacterial community structure across large (e.g., continental, global) spatial scales. One possible explanation for the prevalence of homogeneous selection for bacterial communities on our study islands is the similarity in climate and soil environmental conditions across the islands.…”
Section: Discussionmentioning
confidence: 99%